PROFESSIONALISM, WORK FACILITIES, AND COMPETENCE AS DETERMINANTS OF EMPLOYEE PERFORMANCE THROUGH AFFECTIVE COMMITMENT: EVIDENCE FROM THE BONDOWOSO REGENCY EDUCATION OFFICE - Edi Riyanto; Budi Santoso; Riyanto Setiawan (Universitas Muhammadiyah Bengkulu, 2026)
Effective human resource management plays an important role in improving organizational performance, particularly in the education sector. This study examines the effects of professionalism, work facilities, and competence on the performance of employees at the Bondowoso Regency Education Office, with affective commitment serving as a mediating variable. A quantitative approach was employed using a survey method. The sample consisted of employees of the Bondowoso Regency Education Office selected through an appropriate sampling technique. Data were analyzed using Structural Equation Modeling (SEM) based on WarpPLS to assess both direct and indirect relationships among variables. The findings reveal that professionalism, work facilities, and competence positively and significantly influence employee performance. These variables also positively affect affective commitment, which subsequently mediates their impact on performance. The results support organizational behavior theories emphasizing the role of individual capabilities and workplace conditions in enhancing performance through employee commitment. This study contributes to the literature by extending the understanding of the relationships among professionalism, work facilities, competence, affective commitment, and performance in the public sector. Practically, the findings suggest that organizations should strengthen employee training, improve work facilities, and foster affective commitment to enhance employee performance and the quality of educational services